2014
DOI: 10.19173/irrodl.v15i5.1856
|View full text |Cite
|
Sign up to set email alerts
|

Making ‘MOOCs’: The construction of a new digital higher education within news media discourse

Abstract: One notable 'disruptive' impact of massive open online courses (MOOCs) has been an increased public discussion of online education. While much debate over the potential and challenges of MOOCs has taken place online confined largely to niche communities of practitioners and advocates, the rise of corporate 'xMOOC' ventures such as Coursera, edX and Udacity has prompted popular mass media interest at levels not seen with previous educational innovations. This article addresses this important societal outcome of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 6 publications
(3 reference statements)
0
44
0
3
Order By: Relevance
“…3 Such discussions were also held in professional blogs and magazines (Bulfin, Pangrazio, and Selwyn 2014;White, Leon, and White 2015). A study of three major higher education magazines found that the most important themes discussed in relation to MOOCs were: impact on teaching, change in universities and business models (White, Leon, and White 2015).…”
Section: Media Constructions Of Moocsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Such discussions were also held in professional blogs and magazines (Bulfin, Pangrazio, and Selwyn 2014;White, Leon, and White 2015). A study of three major higher education magazines found that the most important themes discussed in relation to MOOCs were: impact on teaching, change in universities and business models (White, Leon, and White 2015).…”
Section: Media Constructions Of Moocsmentioning
confidence: 99%
“…By means of a thematic analysis of the English-language coverage of MOOCs in Canadian newspapers and professional magazines (2012)(2013)(2014), this paper adds to a small corpus of research on media coverage of MOOCs (Brown 2015;Bulfin, Pangrazio, and Selwyn 2014;Deimann 2015;Kovanović et al 2015;White, Leon, and White 2015). Canada represents an interesting case study in this context: the adoption of new technologies in the field of education has been vigorously supported by the federal government.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is little published discussion on the business and financial aspects of MOOCs (Bulfin, Pangrazio & Selwyn, 2014). Thus critics have questioned of the sustainability of MOOCs.…”
Section: "An Online Course Open To Anyone Without Restrictions (Free mentioning
confidence: 99%
“…As the hype dissipates, there is a sense that the 'disruptive' nature of MOOCs has been cast aside and the phenomenon is being normalised and assimilated into more traditional forms of educational technology practice (Bulfin, Pangrazio & Selwyn, 2014). As MOOCs become heterogeneous, variants are emerging with new identities becoming incorporated into new forms in a reconfiguring landscape (Czerniewicz et al, 2014).…”
Section: Moocs: From Hype To Realitymentioning
confidence: 99%